Prevalence of arterial stiffness in adolescents with type 2 diabetes in the TODAY cohort: Relationships to glycemic control and other risk factors - Shah, Amy S. (J Diabetes Complications, 2018)
AIMS: We aimed to determine the prevalence of arterial stiffness in young adults with youth-onset type 2 diabetes who previously participated in the TODAY clinical trial and whether arterial stiffness is influenced by their prior diabetes treatment assignment or glycemic control. METHODS: We measured arterial stiffness by femoral, radial, and foot pulse wave velocity (PWV), augmentation index (AIx), and brachial distensibility (BrachD) in 453 TODAY participants (age 20.8 ± 2.5 years, diabetes duration 7.6 ± 1.5 years, 36.4% male, BMI 36.7 ± 8.2 kg/m(2)) at a mean of 7.6 years post-randomization. Increased arterial stiffness in TODAY youth was defined compared with data from lean controls. We assessed whether glycemic control over time or diabetes treatment in TODAY was associated with arterial stiffness. RESULTS: Arterial stiffness was identified in up to 50% of TODAY participants. Prior diabetes treatment assignment was not associated with higher arterial stiffness. Glycemic control over time was associated with PWV radial and foot only. Age, race-ethnicity, sex, higher blood pressure and BMI were also associated with higher arterial stiffness. CONCLUSIONS: Nearly half of TODAY youth have increased arterial stiffness. Targeting blood pressure and perhaps obesity and glycemic control may positively impact arterial health in adolescents with type 2 diabetes.